Leif Eriksson : Viking explorer of the New World - DeFries, Cheryl L. (Berkeley Heights, NJ : Enslow Publishers, 2010)
"Examines the life of Viking explorer Leif Eriksson, including his explorations, his discovery of North America, and his legacy in American history"--Provided by publisher.
Who discovered North America? -- Leif Eriksson's family tree -- Leif Eriksson's first voyage -- A major discovery -- Vikings' contributions -- Recognition of Leif Eriksson's accomplishments.
10 - 13 years
Keywords: Leiv Eiriksson -- d. ca. 1020; Explorers -- America; Explorers -- Scandinavia; Vikings; America -- Discovery and exploration -- Norse